DEPOSITION OF ORGANIC CARBON IN AGROBIOGEOCENOSES OF THE TEMPERATE ARID STEPPE OF ALTAI - Andrey E. Kudryavtsev; Evgeny S. Vaganov (Siberian Journal of Life Sciences and Agriculture)
Background. The deposition of organic carbon in biogeocenoses depends on natural conditions. In agrobiocenosis, along with natural conditions, this process is activated by anthropogenic actions in the form of an agricultural system, having studied which can be taken as a basis for the organization of carbon farming.